Network survivability analysis modeling approach for MANETS: A systematic review - Azni A.H.; Ahmad R.; Noh Z.A.M.; Hazwani F.; Hayaati N. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus